Investigation of the dynamics of the viral immediate-early protein 1 in different conformations and oligomerization states - Stump, Joachim; Sticht, Heinrich (Journal of Biomolecular Structure & Dynamics, 2016)
The viral immediate-early protein 1 (IE1) is crucial for efficient replication of cytomegalovirus (CMV). A recent crystal structure of the IE1 protein from rhesus CMV revealed that the protein exhibits a novel fold and crystallizes in two slightly different dimeric arrangements. Molecular dynamics simulations and energetic analyses performed in this study show that both dimers are stable and allowed us to identify a common set of five residues that appear particularly important for dimer formation. These residues are distributed over the entire dimer interface and do not form a typical hot spot for protein interactions. In addition, the dimer interface of IE1 proved to include a high portion of hydrophilic interactions pointing toward the transient nature of dimer formation. Characterization of monomeric and dimeric IE1 revealed three sequentially discontinuous dynamic domains that exhibit correlated motion within the domain and are simultaneously anti-correlated to the adjacent domains. The hinge motions observed between the dynamic domains increase the shape complementarity to the coiled-coil region of tripartite motif proteins, suggesting that the detected dynamics of IE1 might be physiologically important by enabling a better interaction with its cellular target molecules.
EVALuna2:26295